Multi-omics reveals that NOTCH1 promotes cervical cancer progression and reduces radiosensitivity - Guo, Aihua; Su, Zhixiong; Zhang, Enhuan; Lin, Huaqin; Zhong, Peilin; Xie, Zhiyuan; Zhan, Qingzhen; Ye, Ting; Sun, Yang (Frontiers in Immunology, 2025)
BackgroundCervical cancer is the fourth most common malignancy in women globally. The NOTCH signaling pathway is aberrantly activated in multiple tumors, and NOTCH1, its core transmembrane receptor, is highly expressed in cervical cancer. However, NOTCH1’s mechanisms in cervical cancer progression and radiotherapy resistance, as well as its interaction with key molecules, remain unclear.MethodsThis study explored the role of NOTCH1 in cervical cancer from multi-omics perspectives, including single-cell sequencing, cDNA microarrays, high-throughput sequencing, and immunohistochemistry, combined with a series of in vitro and in vivo experiments.ResultsNOTCH signaling activity was negatively correlated with the overall survival and recurrence-free survival of cervical cancer patients. As the core molecule of this signaling pathway, NOTCH1 was significantly highly expressed in cervical cancer tissues and promoted cervical cancer cell proliferation in vitro. Single-cell analysis revealed that NOTCH1 was relatively highly expressed in CPA6+ and CEL+ malignant cells and involved in cell cycle regulation; further cell cycle detection assays confirmed that NOTCH1 could promote the G1-S phase transition. In addition, patients with high NOTCH1 expression showed decreased plasma cell infiltration in the microenvironment. Cell communication analysis indicated that malignant cells with high NOTCH1 expression might lead to impaired plasma cell differentiation due to the impairment of the MIF ligand-receptor pathway. Finally, NOTCH1 could reduce the radiosensitivity of cervical cancer cells to radiotherapy both in vitro and in vivo; whereas has-miR-449a, as an upstream regulatory miRNA of NOTCH1, could inhibit cervical cancer cell proliferation and enhance radiosensitivity by inhibiting NOTCH1 expression.ConclusionsThis study clarifies NOTCH1’s role in promoting cervical cancer progression and reducing radiosensitivity, with has-miR-449a as a negative regulator, providing targets for optimizing cervical cancer radiotherapy.